A study on design & development of betamethasone acetate and betamethasone sodium phosphate extended-release suspension - Bansal, Amit; Sardana, Satish; Wadhwa, Tarun (Journal of Applied Pharmaceutical Research, 2025)
Background: The development of an injectable composition of betamethasone sodium phosphate and betamethasone acetate with an equivalent drug release profile to the marketed reference drug product, "Celestone Soluspan®," is highly challenging. To overcome this drug development problem, there is a need for a practical methodology for the preparation and evaluation of injectable compositions. Methodology: Different sterilization methods (Dry Heat Sterilization and Autoclave) and phase methods (two- or three-phase methods) are used for the preparation of the injectable composition of betamethasone sodium phosphate and betamethasone acetate. Two-phase or three phase methods and order of addition of excipients during the preparation of the formulation are the unique methodology of the present study and plays an important role in the stability of the composition. The release profile of the developed formulations is determined by using a USP type IV dissolution apparatus (STF buffer pH 7.4 as dissolution medium, 6.0 ml/min flow rate for 120 min), and stability study is also performed. Results and Discussion: As per the results of the present study Trial no. 3 shows betamethasone freebase 2.68% and total impurities 3.52% at 40°C /75% RH for 90 days and also gives similar release profile (f2 value 95%) as compared to the marketed formulation/RLD (Reference Listed Drug) i.e. Celestone Soluspan®. Conclusion: Present study concludes that injectable suspension of betamethasone sodium phosphate and betamethasone acetate using dry heat sterilisation of betamethasone acetate and three-phase method shows superior results or equivalent release profile as compared to the RLD and the key features of the present study.